2013
DOI: 10.15376/biores.8.2.1675-1696
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Oil Palm Trunk Waste for Manufacturing of Binderless Particleboard: Optimization Study

Abstract: Utilization of oil palm trunk waste for production of environmental friendly binderless particleboard was studied. Response surface methodology was used to optimize the manufacturing conditions. The steaming temperature (100 to 120˚C), steaming time (25 to 50 min), hot pressing temperature (180 to 220˚C), and hot pressing time (15 to 30 min) were optimized in the ranges shown. The optimum conditions for making the particleboard were found to involve steaming for 46 min at a temperature of 120˚C before it was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 14 publications
3
18
0
2
Order By: Relevance
“…Bell-shaped granules were also observed. This outcome was almost similar to the explanations by Hashim et al (Nadhari et al, 2013). Furthermore, from the apparent particle fractions, a minor fraction of OPTS particles represented hourglass structure along with almost areolate shape including several trumpet-like swellings.…”
Section: Sem-edx Investigations Outcomessupporting
confidence: 89%
See 1 more Smart Citation
“…Bell-shaped granules were also observed. This outcome was almost similar to the explanations by Hashim et al (Nadhari et al, 2013). Furthermore, from the apparent particle fractions, a minor fraction of OPTS particles represented hourglass structure along with almost areolate shape including several trumpet-like swellings.…”
Section: Sem-edx Investigations Outcomessupporting
confidence: 89%
“…1. Bonding arrangement of oil palm trunk (Nadhari et al, 2013) The highest reported OPTS yield was 7.15% of OPT dry weight by using Modified Dos Method (Noor et al, 1999), beating C5/C6 sugars steeping method with lactic acid (1.7% yield) and conventional C5/C6 sugars steeping method (H'ng et al, 2011) although OPT contains 16-17% of extractable starch (Nadhari et al, 2013). To date, there is no comprehensive explanation is available on implementing the bisulfite steeping method for the extraction of starch from oil palm biomass.…”
Section: Introductionmentioning
confidence: 99%
“…This high IB value made from the hydrothermal pretreated E. grandis could be explained based on intermolecular hydrogen bonding between the cellulose and lignin molecule [28]. In accordance with this, a board absorption band appearing in the 3312 -3344 cm −1 region in the hydrothermal pretreated fibers and binderless panels indicated OH stretching in the Fourier- transform infrared (FT-IR) spectra in the Supporting information of Additional file 1: Figure S1 and the data shown in Table 3.…”
Section: Mechanical Properties Of the Binderless Boardssupporting
confidence: 68%
“…Particleboards have been generated using various species of palm trees as the main material such as date palm (Nemli et al 2001;Hegazy and Aref 2010;Amirou et al 2013;Saadaoui et al 2013;Hegazy et al 2015), Washingtonia palm (García-Ortuño et al 2013), and oil palm (Laemsak and Okuma 2000;Hashim et al 2011a;Rasat et al 2011;Suhaly et al 2012;Wad Nadhari et al 2013;Jumhuri et al 2014;Henao et al 2014;Tajuddin et al 2016). The behavior of the particleboard depends on the species of palm tree and the origin of the particles from the trunk or the leaf.…”
Section: Introductionmentioning
confidence: 99%